Mucin Receptors in Chronic Rhinosinusitis with Nasal Polyps - Bedir, Ahmet; Ozgur, Abdulkadir; Bakirtas, Mustafa; Ozdemir, Dogukan; Mehel, Dursun Mehmet; Akgul, Gokhan; Celebi, Mehmet (Taylor & Francis Ltd, 2022)
Background Nasal polyps (NPs) are non-neoplastic, painless inflammatory lesions of the sino-nasal mucosa. Nasal polyp physiopathology is not yet fully understood. There are many potential etiologies of NP, including chronic infections, allergies, asthma, aspirin sensitivity, anatomical disorders, and genetic causes. Objective The purpose of our study was to immunohistochemically demonstrate the presence of mucin (MUC) receptors in chronic rhinosinusitis (CRS) with nasal polyps and determine the relationships between the presence of these receptors and clinical findings. Material and Methods A total of 59 patients who underwent functional endoscopic sinus surgery due to CRS with NPs were included in the study. Groups with positive and negative MUC receptors were evaluated according to their clinical characteristics. Results According to the data we have obtained, surgery site quality and low-dose steroid response worsened with MUC5A receptor positivity and there were no significant relationships between MUC1 receptor positivity and clinical findings. Conclusion According to our results, MUC5A receptor positivity was associated with impaired surgical site quality and a reduced response to low-dose systemic steroids by NPs.
Özgür, Abdulkadir/0000-0002-6155-5988; Bedir, Ahmet/0000-0002-1947-7277; Akgül, Gökhan/0000-0003-0699-6585; Bakirtas, Mustafa/0000-0003-3185-6947; Ozdemir, Dogukan/0000-0003-2008-163X
Keywords: Nasal Polyp; Chronic Sinusitis; Mucin Receptors